Poly(vinyl acetate-co-ethylene) particles prepared by surfactant-free emulsion polymerization in the presence of a hydrophilic RAFT/MADIX macromolecular chain transfer agent. Issue 46 (6th November 2020) - Delorme, James; Boyron, Olivier; Dugas, Pierre-Yves; Dufils, Pierre-Emmanuel; Wilson, D. James; Monteil, Vincent; D'Agosto, Franck; Lansalot, Muriel
Abstract : Poly(vinyl acetate- co -ethylene) latexes are prepared under a broad range of conditions by emulsion polymerization in the presence of a hydrophilic RAFT/MADIX macromolecular chain transfer agent. Abstract : Poly(acrylamide- co -acrylic acid) (P(AAm- co -AA)-X) was prepared by RAFT/MADIX and used as a hydrophilic macromolecular chain transfer agent (macroCTA) in the aqueous emulsion copolymerization of vinyl acetate (VAc) and ethylene. Stable latexes were obtained over a broad range of conditions with macroCTA contents ranging from 1 to 65 wt% (compared to the initial amount of VAc) and ethylene pressure from 10 to 100 bar. The different systems investigated generated latexes incorporating amorphous to semi-crystalline poly(vinyl acetate- co -ethylene) (P(VAc- co -E)) chains using macroCTA content as low as 1 wt% in the absence of additional surfactant. The particle nucleation mechanism was investigated with the help of kinetic studies using cryogenic transmission electronic microscopy (cryoTEM) and was consistent with the concepts underlying polymerization-induced self-assembly (PISA). High solids content latexes were finally targeted with a formulation more in line with industrial constraints (0.4 wt% macroCTA, 35 bar ethylene pressure, semi-batch conditions). A stable P(VAc- co -E) latex was produced exhibiting a solids content of 38 wt%. This work provides an easy access to a full range of alternative stabilization modes for P(VAc- co -E) latexes and potentially to new VAE and EVA products.